Notary Legal Protection on Making Agreement of Sale and Purchase to The Parties - Yanti Herlianti; Sri Praptini; Sri Endah Wahyuningsih (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
In practice of the problem of the degradation of the authentic act can occur because of negligence and / or lack of rigor / carelessness of a Notary resulting in a deed made degraded strength of evidence or null and void.The aim of research in this paper is to determine the responsibility of the Notary deed purchase agreement to the parties and to determine the legal protection against the manufacture Notary deed of sale and purchase agreement to the parties.This study uses normative juridical approach, using a primary law, especially regarding legislation law on Notary. In this study, the data collected through the study of documents and literature.Responsibilities of the Notary civilly against the deed he had done, namely the engagement made by two or more parties despite allowing made unilaterally (in nature only strengthens). MKN is not in providing a legal protection for the Notary as an institution that is independent, because in this case the existence of MKN not a sub part of the government who appointed him. MKN to exercise its authority issued a decision is not influenced by the parties or other institutions, so in this case generated by MKN decision is not inviolable.Keywords: Legal Protection; Notary Deed.